Design the local square for qualitative upgrading and preserve historical identity Case study: central square of Tabriz gharamalek - sara ghahri lalaklou; rasool darskhan (تحقیقات کاربردی علوم جغرافیایی)
today, the importance of the square that have once been a place of interaction for city dwellers, has diminished. the purpose of this study was to identify the effective parameters on improving the quality of space and preserving the historical identity of the square and organizing the square by providing scientific and practiced solutions to enhance the quality of space and preserve its historical identity. This research is of descriptive-analytical type and the statistical population in the present study are people  in square .random  sampling from people of different ages and insights , after starting with the least number , continued until we reached the theoretical saturation of research.the data collection tools are field and library.the analysis was in the form of an open and closed-ended questionnaire that the validity of the questionnaire was assessed as face validity (experts opinion) . and  whit using the swot technique and spss software were analyzed. among the various items to memorize the square , the name of Gharamalek square with 59.3 % is reminiscent of the historical  and valuable space and with naming this space a living historical place is embodied in people's minds.the sum of factors and applications such as the comprehensive mosque , the historical bath , the silk road and etc have been instrumental in establishing the identity of the square.the silk road that used to cross this area in the past and is not known today , ad a negative effect on people's mental image. Conclusion: whit designing and improving the quality of space can transform the square to enhance the level of social relations that different groups of people can attend into a collective space.and strengthening and spatial bonding and visual of square elements can be effective in creating an attractive centrality for the whole neighborhood.